CURRENT ISSUES OF IMPLEMENTATION OF LEGISLATIVE REGULATIONS IN ENVIRONMENTAL PROTECTION AND ENERGY EFFICIENCY AND HEALTH CARE (CLINICAL RESEARCHES) - Dyussenov, Ербол Абаевич; Lyambekova, Арман Каиргельдыевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
Annotation. This article is devoted to the improvement of legislation in the field of environmental protection and health, in particular with regard to clinical researches. The analysis on the compliance of the concept of the Environmental code, the draft Law “On amendments and additions to certain legislative acts of the Republic of Kazakhstan on health issues” to strategic and program documents of the Republic of Kazakhstan was conducted, and an analysis was conducted from the standpoint of providing a favorable environment and free will to conduct clinical researches. Revealed the relevance of studying certain aspects of the normative regulation of relations on a number of environmental problems in Kazakhstan and the validity of the use of drug research in certain categories of the population. The article points out the need for resolving, at the legislative level, the existing environmental issues and the qualitative filling of the concept of the new Environmental code. Based on an analysis of law enforcement practice and a review of the opinions of practitioners, specific issues are identified for a tangible improvement in the environmental situation in cities and in extractive industries, which are regulated by a production-sharing agreement. There were studied issues of ensuring the collection of household waste. There were formulated specific objectives in the field of environmental protection in the context of intersectoral and interdepartmental researches (jointly with the Academy of Law Enforcement Agencies under the General Prosecutor's Office of the Republic of Kazakhstan), considering the provisions of the Concept on the transition of the Republic of Kazakhstan to a "green economy". The need to establish at the legislative level a transparent and effective mechanism for continuous monitoring and control of the cleanliness of vehicle exhaust and the quality of motor fuel sold to the population has been identified. It is proposed to use in relation to gas stations urgent measures of restraint to ban the sale of fuel and for the population to subsidize the replacement of inefficient exhaust catalysts. The author's opinions are given about development of legislative regulation of problematic issues, both in the field of ecology and health, as well as on the need for an accurate review of the best practices of OECD member states. This article contains the author's position on issues, that are closely related to ensuring the vital rights to a favorable environment and health.